Металлургия дуговой сварки конструкционных сталей и сварочные материалы - Походня, И.К. (Автоматическая сварка, 2008)
Review is made of the results of investigations, carried out at the E.O. Paton Electric Welding Institute, on the problems of metallurgy of arc welding of structural steels and development of welding consumables. Problems of arc stability and electrode metal transfer, evaporation of metal and slag, formation of aerosols, interaction of metal with gases and problems of porosity, modeling of interaction in multi-component systems, such as metal–gas, metal–gas–slag, chemical inhomogeneity, crystalline cracks, non-metallic inclusions in welds are described. Investigations of systems of alloying and prediction of weld metal microstructure were made, problem of formation of hydrogen-induced cold cracks in welded joints of high-strength low-alloy steels is elucidated. The achievements of the Institute in the development of new welding consumables are shown and the trends of future research works are outlined.